Development of Learning Media Integrated with Problem Based Learning Model Using Android-Based Application - Yosi Santika Silitonga; Zainuddin Muchtar (Universitas Negeri Medan, 2023)
Technological advances affect education in terms of the use of learning media. This is because the educational process is urged to improve the quality of learning by creating more applicable and interesting learning. Mobile technology can be used as an alternative learning media because the use of mobile devices is very much opens the opportunity in the education process. The aim of this study is to develop a learning media integrated with problem based learning model using android-based application. The development model used is the 4D model which consists of 4 stages, namely Define, Design, Develop and Disseminate. The results of the research are 93.8% agreeing with the existence of android learning media for chemical bonding subjects, the feasibility of the material from the learning media overall obtained 90.1% categorized as “very valid”, and the eligibility of the media as a whole the validator was obtained at 87.39% with the “very valid” category and results of student responses to the developed media as a whole obtained an average value of 80.69% in the “very good” category so that the developed of learning media received a very good response from students